KECURANGAN AKADEMIK: FRAUD DIAMOND, PERILAKU TIDAK JUJUR, DAN PERSEPSI MAHASISWA - Anggun Putri Ramadhan; Endang Ruhiyat (JABI (Jurnal Akuntansi Berkelanjutan Indonesia), 2020)
Academic cheating, especially those committed by students, is a worrying phenomenon that should not occur. Dishonest behavior is one of the factors causing the fraud. Pressure, opportunity and rationalization are other factors that cause students to cheat. The purpose of this study was to determine the analysis of diamond fraud p, dishonest behavior, and student perceptions influence academic cheating, the control variables used were religiosity and technological progress. This research approach is a mix method (mix methods). The object of research is Pamulang University S1 Accounting Study Program in odd semester 2018/2019 with a sample of 142 people. All questions are submitted via Google Drive. For data processing using SPSS version 22. The result of data processing requires diamond fraud to have a significant positive effect on academic fraud. There are 1.5% of students stating academic cheating related to the absence and collusion during exams, this is due to the pressure and ability of more than the individual student. And 3.9% of students are proven to have plagiarism when e-learning and writing papers, this is done because of the often wrong rationalization of unscrupulous students. Person of the student usually justifies what he usually does not accustom the right. Student perceptions and dishonest behavior did not have a significant effect on academic fraud. Keywords:   Fraud diamond; dishonest behavior; student perception; academic cheating